2016
DOI: 10.1177/0040517515624874
|View full text |Cite
|
Sign up to set email alerts
|

Development of an enzyme-immobilized support using a polyester woven fabric

Abstract: In this study, we aimed to develop an enzyme-immobilized support using polyester woven fabrics and to optimize the development process. We obtained information about the storage stability and reusability of the enzyme and showed the applicability of the polyester woven fabric as an enzyme-immobilized support. In particular, the samples hydrolyzed by hydrogen chloride were treated with N,N'-dicyclohexylcarbodiimide and N-hydroxysuccinimide to activate the surfaces. We evaluated the relative activity of the enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Textile dyeing technologies, through which fabrics are imparted with different colors using dyeing chemistry to manufacture the final textile products, provided an inspiring idea for catalyst immobilization. First, fabrics produced from cotton, polyamide, or polyester are promising carriers for catalyst immobilization due to the following advantages: (1) good mechanical properties, excellent durability, high chemical resistance, smooth surfaces, and good processability; , (2) the intrinsic flexibility of fabrics makes them capable of being fitted in any reactor geometry and being separated easily without leaving any residues; (3) pore diffusion, which will influence the reactivity of the catalyst, can also be avoided due to the smooth fabric surface; (4) pendant groups on the surface of the polymeric fabrics, for instance, hydroxyl groups on the surface of cellulosic fabrics, or amino groups on the wool fabrics, are powerful moieties for anchoring catalysts; , (5) manufacturing costs for fabrics are much lower than other solid supports, which is especially true for cotton considered as a nearly inexhaustible natural source for fabric production. , Therefore, a variety of bioactive molecules and organocatalysts have been extensively immobilized on fabrics made of cotton, , wool, polyester, , poly­(ethylene terephthalate), ,, poly­(vinyl alcohol), and poly­(amide 6.6). ,, …”
Section: Introductionmentioning
confidence: 99%
“…Textile dyeing technologies, through which fabrics are imparted with different colors using dyeing chemistry to manufacture the final textile products, provided an inspiring idea for catalyst immobilization. First, fabrics produced from cotton, polyamide, or polyester are promising carriers for catalyst immobilization due to the following advantages: (1) good mechanical properties, excellent durability, high chemical resistance, smooth surfaces, and good processability; , (2) the intrinsic flexibility of fabrics makes them capable of being fitted in any reactor geometry and being separated easily without leaving any residues; (3) pore diffusion, which will influence the reactivity of the catalyst, can also be avoided due to the smooth fabric surface; (4) pendant groups on the surface of the polymeric fabrics, for instance, hydroxyl groups on the surface of cellulosic fabrics, or amino groups on the wool fabrics, are powerful moieties for anchoring catalysts; , (5) manufacturing costs for fabrics are much lower than other solid supports, which is especially true for cotton considered as a nearly inexhaustible natural source for fabric production. , Therefore, a variety of bioactive molecules and organocatalysts have been extensively immobilized on fabrics made of cotton, , wool, polyester, , poly­(ethylene terephthalate), ,, poly­(vinyl alcohol), and poly­(amide 6.6). ,, …”
Section: Introductionmentioning
confidence: 99%
“…Further experiments would be needed to determine if this hypothesis is valid. When redissolved in buffer, the EFSBN webs showed at least 60% of their initial activity after 300 days, which is higher than the residual activities of immobilized protease in various polymeric supports reported in the literature as only 33–57% after a much shorter storage period of 30 days at 4 °C. ,, This result revealed that immobilized protease in EFSBN could be conveniently stored at ambient temperature or in refrigerators. The produced EFSBN are a unique storage technique in a quick-dissolving solid form rather than typical liquid enzymes or lyophilized forms.…”
Section: Resultsmentioning
confidence: 61%
“…When redissolved in buffer, the EFSBN webs showed at least 60% of their initial activity after 300 days, which is higher than the residual activities of immobilized protease in various polymeric supports reported in the literature as only 33−57% after a much shorter storage period of 30 days at 4 °C. 17,65,66 This result revealed that immobilized protease in EFSBN could be conveniently stored at ambient temperature or in refrigerators.…”
Section: Storage Stability and Thermal Stability Of Efsbn And Native ...mentioning
confidence: 84%
“…Several studies have reported the effect of spacer length and type of spacer between enzyme and carrier and its effect on the activity of the immobilized enzyme [ 38 , 46 , 47 ]. Higher activity is observed when a spacer is incorporated between the carrier and enzyme to reduce steric hindrance, promote conformational mobility, and reduce adverse surface interaction [ 18 , 19 , 48 ]. A spacer was introduced to the PVA-Cl discs by reaction with diamine in ethanol and resultant amine was reacted with glutaraldehyde [ 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%